Romanticism in the Poetry of Hushang Ebteaj - محمد امین محمدپور; علی اصغر باباصفری (مطالعات زبانی و بلاغی)
Literary school of romanticism was founded in the nineteenth century by breaking the fetters of classical school. Preference of feeling to wisdom, tendency toward nature and homeland and also dealing with feelings such as love-grief-and naturalism were among the major changes of this school. H. E   is one of the great contemporary poets and principles of romanticism govern most of his poems.  Most important areas of romantic thoughts in the poetry of H. E include:  love - grief- remembrance of the death – soliloquy – homeland -naturalism- hope- idealization. H. Ebtehaj writes of his existential "I" in the field of individualistic romanticism and talks of "I" in the form of "We" in society-oriented romanticism, and speaks about community. Romanticism in the poetry of H.E will be studied in a descriptive and content analysis way in this article.